2017
DOI: 10.1007/s00330-017-4885-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of T1 perfusion-based classification in magnetic resonance-guided high-intensity focused ultrasound ablation of uterine fibroids

Abstract: • MRI is an important modality for outcome prediction in HIFU treatment • Patient selection is a significant factor for achieving high NPV ratio • NPV ratio is very strongly correlated with T1 perfusion-based classification • T1 perfusion-based classification is a strong predictor of treatment outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 26 publications
4
50
0
Order By: Relevance
“…The perfusion analysis showed enhanced blood flow in the region of the myoma when compared to the surrounding myometrium. A high perfusion 13 rate has a strong cooling effect which has been shown to be a significant predictor of treatment outcome (Keserci and Duc, 2017). It has previously been reported that the perfusion of the uterine fibroids varies on average between 50-334 mL/100 g/min, which supports that the fibroid in this study had relatively high perfusion rate (Wei et al, 2018).…”
Section: Discussionsupporting
confidence: 78%
“…The perfusion analysis showed enhanced blood flow in the region of the myoma when compared to the surrounding myometrium. A high perfusion 13 rate has a strong cooling effect which has been shown to be a significant predictor of treatment outcome (Keserci and Duc, 2017). It has previously been reported that the perfusion of the uterine fibroids varies on average between 50-334 mL/100 g/min, which supports that the fibroid in this study had relatively high perfusion rate (Wei et al, 2018).…”
Section: Discussionsupporting
confidence: 78%
“…Recently, a new classification method based on MRI T1 perfusion-based time-SI curves for fibroid tissue compared with those for the myometrium in screening MRI was introduced by Keserci et al (20) for predicting the treatment outcome of HIFU ablation. The fibroids were classified into group A if the time-SI curve was lower than that for the myometrium (Fig.…”
Section: Main Pointsmentioning
confidence: 99%
“…Clinical studies (7,20,39,40,45) suggested that the cells to be treated must be located on the T2-weighted planning images, and the safety margin or distance from the border of the cells to be treated to critical organs such as the sacral bone should be taken into consideration (e.g., 4 cm), since heat accumulation in the bone can subsequently be transferred to the perineural fat and adjacent nerves. The adverse effects encountered in these studies were partly related to far-field heat absorption by distant bony structures (e.g., sciatic nerve symptoms).…”
Section: Distance Between Sacral Bone Surface and Uterine Fibroidsmentioning
confidence: 99%
“…MRI examination revealed that there were 15 uterine leiomyomas affected almost areas of anteflexed uterus considered as all type II uterine leiomyomas (the signal intensity of leiomyoma was greater than that of skeletal muscle and less than that of myometrium) (FIGURE 3A) [2]. The perfusion classification of uterine leiomyomas was regarded as type A uterine leiomyoma (the time signal intensity curve of uterine leiomyoma was less than that of myometrium) (FIGURE 3B) [3]. The patient was indicated single phase HIFU surgery under the guidance of magnetic resonance imaging by which clinician utilized 40 treatment cells (12 mm, n=12; 14 mm, n=18; 16 mm, n=10) and a mean power of 158 ± 26W.…”
Section: Resultsmentioning
confidence: 99%
“…Magnetic Resonance Imaging (MRI) guided High-intensity Focused Ultrasound (HIFU) which combines the anatomical and functional imaging of MR with the thermal ablation possibilities of HIFU, is an alternative treatment to hysterectomy for the treatment of uterine fibroids and preserves the uterus [2,3]. In this case report, we aimed to display one tough case of 15 leiomyomas and another tough case of huge leiomyoma ablated profitably by single phase HIFU along with the pros and cons of these findings.…”
Section: Introductionmentioning
confidence: 99%